Pengembangan Video Pembelajaran IPS Berbasis Project-Based Learning pada Materi Kegiatan Ekonomi untuk Meningkatkan Minat Belajar Siswa - Fatimah, Siti; Sadri, Muhammad; Darsih, Try Santi Kisria (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This research aims to develop learning video products based on Project-based Learning and to determine the learning interest of class VII students at SMP IT Adzkia Babalan in social studies learning about economic activities. This type of research is RD with the ADDIE development model which consists of 5 stages, namely: 1) Analysis; 2) Design; 3) Development; 4) Implementation; and 5) Evaluation.  The subjects in this research were 25 students in class VII of SMP IT Adzkia Babalan.  From the validation results of several experts, the results of the material expert validation test were 86.67% and were included in the very feasible category.  The media expert validation results were 89.3% and were in the very feasible category. The learning expert validation results were 76% and were in the feasible category. The increase in interest in learning was shown through data analysis from field trials carried out using a Likert scale and a result of 76.3% was obtained.  Thus, Project-based Learning videos are suitable for use as learning media in the social studies’ subject material for class VII on topic economic activities.